CCL21/CCR7 axis regulates VEGF-D m6A modification to drive lymphangiogenesis and lymphatic metastasis in gallbladder cancer - Zhenheng Wu; Xinran Cai; Lei Jiang; Bin Lin; Wei Pan; Shengzhe Lin; Yanling Chen; Haijie Hong (Human Cell, 2026)
Gallbladder cancer (GBC), the most common malignancy of the biliary tract, exhibits a high propensity for lymphatic system invasion. However, the mechanisms underlying lymphatic metastasis in GBC remain poorly understood. Here, we demonstrate that C–C motif chemokine ligand 21 (CCL21) is significantly upregulated in GBC and positively correlates with lymphatic vessel density and lymph node metastasis. Both in vivo and in vitro experiments confirm that CCL21/CCR7 axis promotes lymphangiogenesis and lymphatic metastasis in GBC. Mechanistically, CCL21/CCR7 modulates Vascular Endothelial Growth Factor-D (VEGF-D) mRNA N6-Methyladenosine (m 6 A) modification in an AlkB homolog 5 (ALKBH5)-dependent manner, thereby regulating VEGF-D protein expression. Site-directed mutagenesis experiments reveal that m 6 A modification sites in the coding sequence (CDS) region of VEGF-D mRNA are critical for VEGF-D protein regulation. Collectively, our findings highlight that CCL21/CCR7 regulates VEGF-D expression via m 6 A modification, driving lymphatic metastasis in GBC.